All-solid-state-supercapacitor and a process for the fabrication thereof - Kurungot, Sreekumar; Badiger, Manohar V.; Anothumakkool, Bihag; Torris, Arun (WO2014170912 A1, 2014)
The present invention discloses. all-solid-state supercapacitor (ASSP) with enhanced electrode-electrolyte interface which gives highest very high specific capacitance, areal capacitance and shows very low internal resistance (ESR). The invention particularly discloses the fabrication of all-solid-state supercapacitor by intercalation of solid state polymer electrolyte inside the conducting porous substrate coated with a charge storage electrode material to achieve the desired effect.

Healable network polymers bearing flexible poly(Lauryl Methacrylate) chains via thermo-reversible furan-maleimide diels-alder reaction - Patil, Sachin S.; Torris, Arun; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
A new ATRP initiator containing two furyl rings, namely, bis(furan-2-ylmethyl) 2-bromopentanedioate was synthesized starting from commercially available L-glutamic acid as a precursor. Well-defined bisfuryl-terminated poly(lauryl methacrylate) macromonomers with molecular weight and dispersity in the range 5000-12,000 g mol(-1) and 1.30-1.37, respectively, were synthesized employing the initiator by atom transfer radical polymerization (ATRP). Independently, 1,1',1"(nitrilotris(ethane-2,1-diyl)) tris(1H-pyrrole-2,5-dione) was synthesized as a tris-maleimide counterpart for furan-maleimide click reaction. Thermo-reversible network polymer bearing flexible poly(lauryl methacrylate; (PLMA) chains was obtained by furan-maleimide Diels-Alder click reaction of bisfurylterminated PLMA with 1,1',1"-(nitrilotris(ethane-2,1-diyl)) tris(1Hpyrrole-2,5-dione). The prepared network polymer showed retro-Diels-Alder reaction in the temperature range 110-170 degrees C as determined from DSC analysis. The presence of low Tg (-40 degrees C) PLMA chains induced chain mobility to the network structure which led to the complete scratch healing of the coating at 60 degrees C in five days due to furan-maleimide adduct formation. The storage modulus of the network polymer was found to be 3.7 x 10(4) Pa at the constant angular frequency of 5 rad/ sec and strain of 0.5%. The regular reversal of storage (G0) and loss modulus (G") was observed with repeated heating (40 to 110 degrees C) and cooling cycles (110 to 40 degrees C) at constant angular frequency and strain. (C) 2017 Wiley Periodicals, Inc.
Keywords: ethane; Monomers; polymerization

Inducing disorder in order: hierarchically porous covalent organic framework nanostructures for rapid removal of persistent organic pollutants - Karak, Suvendu; Dey, Kaushik; Torris, Arun; Halder, Arjun; Bera, Saibal; Kanheerampockil, Fayis; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
The key factor responsible for fast diffusion and mass transfer through a porous material is the availability of a widely open pore interior having complete accessibility from their surface. However, because of their highly stacked nature, ordered two-dimensional (2D) materials fail to find real-world applicability, as it is difficult to take advantage of their complete structure, especially the inner cores. In this regard, three-dimensional (3D) nanostructures constructed from layered two-dimensional crystallites could prove to be advantageous. However, the real challenge is to cultivate a porous nanostructure with ordered pores where the pores are surrounded by crystalline walls. Herein, a simple yet versatile in situ gas-phase foaming technique has been employed to address these cardinal issues. The use of baking soda leads to the continuous effervescence of CO2 during the crystallization of foam, which creates ripples and fluctuations on the surface of the 2D crystallites. The induction of ordered micropores within the disordered 3D architecture synergistically renders fast diffusion of various guests through the interconnected pore network. The high-density defects in the hierarchically porous structure help in ultrafast adsorption (<10 s) of various pollutants (removal efficiency of 99%) from water, all of which would lead to significant environmental benefit. The pseudo-second-order rate constant for the BPA pollutant is 182.3 g mg(-1) min(-1), which is the highest among all the literature reports to date. The high removal efficiency (highest efficiency of 94% and average efficiency of 70%) of a persistent organic pollutant has been attended for the first time.

Mapping fusogenicity of ciprofloxacin-loaded liposomes with bacterial cells - Patil, Runali; Torris, Arun; Bhat, Suresh; Patil, Sharvil (AAPS Pharmscitech, 2019)
The process of liposome fusion with cellular membrane plays key role in delivering encapsulated drug molecule into the cell. This process becomes very important for molecules having low permeability as they fail to reach the site of action located inside the cell. Ciprofloxacin (CIP), a broad-spectrum BCS class IV antibiotic, has poor permeability. In the present work, CIP-loaded liposomes were prepared using solvent evaporation method and optimized by 3(2) factorial design approach. The optimized batch of CIP-loaded liposomes was characterized for size, entrapment efficiency, zeta potential, FTIR, and microbial susceptibility study on Staphylococcus aureus (gram-positive bacteria) and Escherichia coli (gram-negative bacteria). Confocal microscopy was used to study the fusogenicity process of CIP-loaded liposomes with bacterial cells. Additionally, the kinetics of fusogenicity process was studied using SAXS for the first time. Surprisingly, the rate of fusion of CIP-loaded liposomes with cell wall of S. aureus was twice when compared to the cell wall of E. coli. It is believed that the current work can act as a roadmap in selection of proper excipients while developing formulations which would expedite the fusogenicity and may execute pharmacological activity of poorly penetrable drug molecules at lower dose.
Keywords: ciprofloxacin; confocal microscopy; fusion; liposomes; SAXS

Polysaccharide hydrogel incorporated carbon nanofiber microelectrode for designing neural interfaces - Torris, Arun; Badiger, Manohar V. (Journal of Bionic Engineering, 2019)
Bionic devices are an integral part of human life, and continuous innovations in their design and functions with the help of nanotechnology has revolutionized the area of neuroscience and technology. Bio-interfaces play a key role in bionic devices such as neural implants for efficient transfer of the signal to smart prosthetics. We report here on the design of a new microelectrode, comprising Carbon Nanofiber (CNF) and a biopolymer, namely carboxymethyl xyloglucan (CMX) hydrogel inside the CNF, which enhances the current density across the interface. Microelectrode was prepared by in-situ cross-linking of CMX inside CNF, with optimized CMX: CNF ratio, resulting in continuous ionic channels confined within the hollow core of CNF. Electron microscopy images of microelectrodes illustrate the formation of CMX hydrogel network inside the CNF hollow core without wrapping its surface. The presence of hydrogel in the CNF was confirmed by Scanning Electron Microscope (SEM) and Transmission Electron Microscopy (TEM). The electrochemical studies indicate the enhancement in charge density as well as the active surface area of the microelectrodes due to the presence of CMX hydrogel network. These microelectrodes have great potential as neural interfaces for designing smart prosthetics with voluntary control.

Self-assemblies of nucleolipid supramolecular synthons show unique self-sorting and cooperative assembling process - Nuthanakanti, Ashok; Walunj, Manisha B.; Torris, Arun; Badiger, Manohar V.; Srivatsan, Seergazhi G. (Nanoscale, 2019)
The inherent control of the self-sorting and co-assembling process that has evolved in multi-component biological systems is not easy to emulate in vitro using synthetic supramolecular synthons. Here, using the basic component of nucleic acids and lipids, we describe a simple platform to build hierarchical assemblies of two component systems, which show an interesting self-sorting and co-assembling behavior. The assembling systems are made of a combination of amphiphilic purine and pyrimidine ribonucleoside-fatty acid conjugates (nucleolipids), which were prepared by coupling fatty acid acyl chains of different lengths at the 2 `-O- and 3 `-O-positions of the ribose sugar. Individually, the purine and pyrimidine nucleolipids adopt a distinct morphology, which either supports or does not support the gelation process. Interestingly, due to the subtle difference in the order of formation and stability of individual assemblies, different mixtures of supramolecular synthons and complementary ribonucleosides exhibit a cooperative and disruptive self-sorting and co-assembling behavior. A systematic morphological analysis combined with single crystal X-ray crystallography, powder X-ray diffraction (PXRD), NMR, CD, rheological and 3D X-ray microtomography studies provided insights into the mechanism of the self-sorting and co-assembling process. Taken together, this approach has enabled the construction of assemblies with unique higher ordered architectures and gels with remarkably enhanced mechanical strength that cannot be derived from the respective single component systems.

Effect of bio-filler on hybrid sisal-banana-kenaf-flax based epoxy composites: a statistical correlation on flexural strength - Vivek, Somasundaram; Kanthavel, Karuppusamy; Torris, Arun; Kavimani, Vijayananth (Journal of Bionic Engineering, 2020)
This work deals with the investigation of the synergistic effect of bagasse ash with sisal-banana-kenaf-flax fibers reinforced epoxy composite for their flexural behavior. The composites with three combinations of hybrid fibers viz. sisal/kenaf (HSK), banana/kenaf (HBK), and banana/flax (HBF) with bagasse ash (BGA) as filler material are fabricated using vacuum bag assisted resin transfer molding. Experiments were conducted based on L27 orthogonal array to understand the influence of control factor viz. fiber volume, alkali concentration & BGA over output response.X-ray micro computed tomography analysis was conducted over the developed sample to infer the uniform dispersion of fiber and filler material. The experimental results reveal that the addition of fiber up to 30 vol% depicts better strength and further addition results in a negative impact. Increasing in order of BGA decreases the flexural strength of the developed composites.
Keywords: bagasse ash; flexural strength; natural fiber; vacuum bag assisted resin transfer molding; X-ray micro computed tomography

Enhancing the mechanical properties of 3D printed polylactic acid using nanocellulose - Ambone, Tushar; Torris, Arun; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2020)
We report here a systematic investigation of the mechanical properties of polylactic acid (PLA) processed by fused filament fabrication (FFF) 3D printing vs PLA processed by compression molding. Our results show that the tensile strength and modulus of FFF-PLA is 49% and 41% lower, respectively, than compression molded samples of PLA. We also demonstrate here an approach to augment the mechanical properties of 3D printed PLA using nanocellulose. Incorporation of a small quantity (1 wt%) of cellulose nanofibers (CNF) was found to enhance the tensile strength and modulus of 3D printed PLA by 84% and 63%, respectively. X-ray microtomography was used to probe the morphology of 3D printed PLA and PLA/CNF composites. 3D printed PLA/CNF composites had significantly lesser voids as compared to neat 3D printed PLA. Differential scanning calorimetry study revealed that CNF can accelerate the nucleation and crystallization of 3D printed PLA leading to enhanced crystallinity. The thermal stability of 3D printed PLA/CNF composites was not compromised by the addition of CNF. The enhanced mechanical properties of 3D printed PLA/CNF composites can be ascribed to higher crystallinity and lesser defects.
Keywords: 3D printing; Biocomposites; composites; fused filament fabrication (FFF); Nanocellulose; polylactic acid (PLA)

Functionalized single-walled carbon nanohorns to reinforce sulfonated poly(ether ether ketone) electrolyte for direct methanol fuel cells - Turanelloormana, Parameswaran; Sarmah, Sudeshna; Torris, Arun; Bhat, Santoshkumar D.; Unni, SreeKuttan M. (ChemElectroChem, 2020)
Carbon-nanomaterial-based additives are promising materials for improving the physicochemical properties of sulfonated polyether ether ketone (sPEEK) for its use as composite membrane electrolyte in direct methanol fuel cells (DMFCs). In this work, functionalized single-wall carbon nanohorns (f-SWNHs) are realized as an additive in sPEEK. The -COOH groups created on the SWNHs during peroxide treatment improve the dispersion of f-SWNHs in sPEEK and boost the proton conductivity, ion exchange capacity, mechanical properties and reduce the methanol permeability of the electrolyte. The composite membrane with 0.50 wt.% f-SWNHs shows improved electrochemical selectivity of 17.03x10(-4) Scm(-3)s and delivers the highest peak power density of 230 mW cm(-2)in DMFCs.
Keywords: carbon nanohorns; direct methanol fuel cells; membrane electrolyte; proton conductivity; sulfonated poly ether ether ketone

In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries

Design and synthesis of a new topical agent for halting blood loss rapidly: a multimodal chitosan-gelatin xerogel composite loaded with silica nanoparticles and calcium - Patil, Gokul; Torris, Arun; Suresha, P. R.; Jadhav, Sachin; Badiger, V. Manohar; Ghormade, Vandana (Colloids and Surfaces B-Biointerfaces, 2021)
Uncontrolled hemorrhage often causes death during traumatic injuries and halting exsanguination topically is a challenge. Here, an efficient multimodal topical hemostat was developed by (i) ionically crosslinking chitosan and gelatin with sodium tripolyphosphate for (ii) fabricating a robust, highly porous xerogel by lyophilization having 86.7 % porosity, by micro-CT and large pores similar to 30 mu m by SEM (iii) incorporating 0.5 mg synthesized silica nanoparticles (SiNPs, 120 nm size, -22 mV charge) and 2.5 mM calcium in xemgel composite that was confirmed by FTIR analysis with peaks at 3372, 986 and 788 cm(-1), respectively. XPS analysis displayed the presence of SiNPs (Si2p peak for silicon) and calcium (Ca2p1, Ca2p3 transition peaks) in the composite. Interestingly, in silico percolation simulation for composite revealed interlinked 800 mu m long-conduits predicting excellent absorption capacity and validated experimentally (640 % of composite dry weight). The composite achieved >16-fold improved blood clotting in vitro than commercial Celox and Gauze through multimodal interaction of its components with RBCs and platelets. The composite displayed good platelet activation and thrombin generation activities. It displayed high compressive strength (2.45 MPa) and withstood pressure during application. Moreover, xerogel composite showed high biocompatibility. In vivo application of xerogel composite to lethal femoral artery injury in rats achieved hemostasis (2.5 min) significantly faster than commercial Celox (3.3 min) and Gauze (4.6 min) and was easily removed from the wound. The gamma irradiated composite was stable till 1.5 yr. Therefore, the xerogel composite has potential for application as a rapid topical hemostatic agent.
Keywords: Hemostatic; Polymer; silica nanoparticles; Xerogel

Elastic piezoelectric aerogels from isotropic and directionally ice-templated cellulose nanocrystals: comparison of structure and energy harvesting - Ram, Farsa; Biswas, Bipul; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Cellulose, 2021)
We report the preparation of highly compressible and elastic piezoelectric aerogels of carboxylated cellulose nanocrystals (CNCs). Aqueous CNC dispersions containing polyethyleneimine and crosslinker were frozen isotropically to yield isotropic aerogels, while oriented aerogels were prepared by directional freezing. These aerogels were highly flexible and porous (similar to 85% void fraction), exhibiting greater than 90% recovery at 50% compressive strain even after 100 compression-decompression cycles. Since such aerogels with low bulk modulus and high anisotropy would be an ideal platform for leveraging the piezoelectric properties of CNCs, we used them to prepare piezoelectric nanogenerator devices and determined their energy transduction behavior. Anisotropic aerogels led to an enhanced open-circuit voltage of 840 mV (at similar to 8 N applied force), which is over 2.6 times higher than isotropic aerogels (320 mV). The energy density of anisotropic aerogels was around 52 nW/cm(2), representing outstanding piezoelectric performance for cellulose-based aerogels. Such aerogels with high compressibility, elastic recovery and exceptional piezoelectric performance could have potential applications in sensors, wearable electronics, etc.
Keywords: Aerogel; Anisotropic; Cellulose nanocrystals; energy harvesting; Piezoelectricity

Highly compressible ceramic/polymer aerogel-based piezoelectric nanogenerators with enhanced mechanical energy harvesting property - Ram, Farsa; Suresh, Karthika; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Ceramics International, 2021)
Ceramic piezoelectric materials have orders of magnitude higher piezoelectric coefficients compared to polymers. However, their brittleness precludes imposition of large strains in mechanical energy harvesting applications. We report here that ice templating affords low bulk modulus lead-free aerogel piezoelectric nanogenerators (PENG) with unprecedented combination of flexibility and high piezoelectric response (voltage and power density). A modified ice templating protocol was used to fabricate piezoelectric nanocomposites of surface modified BaTiO3 (BTO) nanoparticles in crosslinked polyethylene imine. This protocol allowed incorporating a significantly high fraction of BTO particles (up to 83 wt %) in the aerogel, while retaining remarkably high compressibility and elastic recovery up to 80% strain. The output voltage, at an applied compressive force of 20 N (100 kPa), increased with BTO loading and a maximum output voltage of 11.6 V and power density of 7.22 ?W/cm2 (49.79 ?W/cm3) was obtained for PENG aerogels containing 83 wt% BTO, which is orders of magnitude higher than previously reported values for foam-based piezoelectric energy harvesters. The BTO/PEI PENGs also showed cyclic stability over 900 cycles of deformation. PENGs with higher porosity showed better elastic recovery and piezoelectric properties than lower porosity and higher BTO content aerogels. To the best of our knowledge, this is the first report to demonstrate the piezoelectric properties of high ceramic content aerogels having very high compressibility and elastic recovery.
Keywords: Ceramic polymer aerogels; energy harvesting; ice templating; piezoelectric

Mechanical and microstructural studies in a polysaccharide-acrylate double network hydrogel - Torris, Arun; Nair, Sanoop; Mol, K. P. Raji; Sengupta, Poulomi; Badiger, Manohar (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
Polymeric hydrogels continue to find a wide range of applications. However, a major drawback of hydrogels is the lack of mechanical strength. In this regard, ``Double Network Hydrogels'' (DN) have shown great promise recently. The toughness in DN hydrogels originates from the synergistic effect of two polymeric networks. In this work, we have synthesized a DN hydrogel consisting of a tightly cross linked carboxymethylcellulose (CMC) as the first network and loosely cross linked poly(hydroxyethylacrylate) (PHEA) as a second network (CMC-PHEADN). The required flexibility in the second network (PHEA) was induced by the presence of a small amount of stearyl methacrylate (SM) as a co-monomer in hydroxyl ethyl acrylate (HEA). The compressive strength of the CMC-PEHA-DN hydrogel was found to be 280 times more than that of CMC-SN hydrogel, and the presence of SM in DN hydrogels showed better recovery after deformation. Cell viability studies showed the biocompatibility of DN hydrogels. The micro-structural analysis of DN xerogels by 3D X-ray Microtomography indicated the presence of oriented pores in size range of 30-40 mu m. To the best of our knowledge, Microtomography was used for the first time to study the DN gels. These hydrogels can be used to develop implants that can withstand prolonged stress and expand the life span of implants.
Keywords: Carboxymethyl cellulose; Double network hydrogels; Poly(hydroxyethyl acrylate); Poly(hydroxyethyl-co-stearyl methacrylate)

Micro-computed tomographic analysis of the marginal adaptation of a calcium silicate-based cement to radicular dentin after removal of three different intracanal medicaments - an in vitro study - Jain, Ruchika Nirmal; Abraham, Sathish; Karad, Rohini Ramesh; Najan, Harshal Balasaheb; Vaswani, Sneha Dhruvkumar; Torris, Arun (Journal of Conservative Dentistry, 2021)
<p style="box-sizing: inherit; line-height: 1.5; margin-top: 1.2rem; margin-bottom: 1.2rem; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Context: This study focuses on the marginal adaptation of a calcium silicate-based cement to the root dentin after retrieval of different intracanal medicaments. <p style="box-sizing: inherit; line-height: 1.5; margin-top: 1.2rem; margin-bottom: 1.2rem; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aim: This study compared the marginal adaptation of a calcium silicate-based cement to radicular dentin in the apical third of the root canal following the use of three different intracanal medicaments. <p style="box-sizing: inherit; line-height: 1.5; margin-top: 1.2rem; margin-bottom: 1.2rem; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Materials and methods: Forty single-rooted premolar teeth (n = 40) were decoronated 13 mm above the root apices; then, 3 mm of the root tips were resected to standardize the root length. Orthograde cleaning and shaping were done using the rotary files and apical enlargement using peeso reamers. Depending on the intracanal medicament used, the samples were equally divided into four groups: Group 1 - control, Group 2 - Metapex, Group 3 - triple antibiotic paste (TAP), and Group 4 - calcium hydroxide with Propolis. Subsequently, the medicament was removed and a 3 mm apical barrier of BiodentineTM was placed and later scanned using an ex vivo micro-computed tomography scanner.

Resveratrol loaded cubic phase nanoparticles with enhanced oral bioavailability - Rawat, Neeraj Kumar; Torris, Arun; Bhat, Suresh; Mahadik, Kakasaheb; Patil, Sharvil (BioNanoScience, 2021)
Resveratrol (RES), a naturally occurring hydrophobic polyphenolic compound, has shown potential anticancer activity. However, due to low aqueous solubility and extensive first pass metabolism (primarily by cytochrome enzymes), it shows poor oral bioavailability. In the present work, novel RES loaded cubosomes of glycerol monooleate (GMO) and Gelucire 44/14 (GL44) (RES-Cubs) were prepared. RES-Cubs were prepared by emulsion evaporation technique and optimized using 32 factorial design. The optimized RES-Cubs were assessed for particle size, zeta potential, entrapment efficiency, FTIR, TEM, SAXS, in vitro resveratrol release and oral bioavailability. RES-Cubs showed an average particle size of 121.7 ± 2.54 nm with adequate entrapment efficiency of about 82.0 ± 2.35% w/w. The analysis of SAXS profile of RES-Cubs revealed Pn3m crystallographic space group containing diamond cubic phase. In vitro RES release profile of RES-Cubs exhibited markedly sustained release of resveratrol. Furthermore, RES-Cubs demonstrated considerable enhancement in oral bioavailability (ninefold) of resveratrol as compared to RES alone. The developed RES loaded cubosomes bearing cytochrome enzyme inhibitor property can act as promising nanocarrier in the delivery of lipophilic drugs with a drawback of in vivo degradation by cytochrome enzymes.

Sulfonated polyvinyl alcohol ionomer membrane favoring smooth electrodeposition of zinc for aqueous rechargeable zinc metal batteries - Vijayakumar, Vidyanand; Torris, Arun; Kurian, Maria; Mathew, Megha Mary; Ghosh, Meena; Khairnar, Ajay B.; Badiger, Manohar V.; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2021)
One of the failure mechanisms of aqueous rechargeable zinc metal batteries (AZMBs) involves high surface area zinc (HSAZ)/dendrite-like deposits over the Zn-metal anode during long-term cycling. Negatively charged (anionic) polymeric ionomer electrolyte membranes and separators are known for suppressing the dendrite-/HSAZ-induced failure of AZMBs. However, the preparation of cost-effective and non-fluorinated ionomers from cheap and environmentally friendly polymers is essential to leverage the feasibility of AZMBs. The current work demonstrates the potential of an ionomer electrolyte membrane (P-AS-C-Zn) made by the crystallization-induced physical cross-linking of sulfonated poly (vinyl alcohol) (PVS) and poly (vinyl alcohol) (PVA) as a dendrite-/HSAZ-inhibiting separator for AZMBs. The P-AS-C-Zn membranes exhibited excellent Zn plating/stripping behavior with a stable voltage vs. time profile beyond 1100 h, compared to their neutral PVA-C-Zn counterpart without any ionomer character (cell failure at close to 280 h). Applying the optimized P-AS-C-Zn membrane in a MnO2||Zn full cell helps retain about 50% of the initial capacity close to 600 cycles in the absence of extra manganese salt in the electrolyte, which is indeed promising.

Tuning the selectivity of CO2 hydrogenation using ceramic hollow fiber catalytic modules - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Kharul, Ulhas K.; Naidu, V. Satyam; Devi, R. Nandini (Reaction Chemistry & Engineering, 2021)
The unique structural features and advantageous pore distributions of alumina hollow fibers can be exploited to tune the selectivity in heterogeneous catalysis. Formation of a finger-like cavity structure is the unique characteristic of the phase inversion method, which provides a larger surface area to volume ratio desirable for catalytic reactions. This feature, along with a highly porous sandwiched skin layer, makes this architecture superior to conventional powder catalysts or other structured catalyst forms like monoliths. Alumina hollow fibers are prepared by the modified phase inversion method and characterized for their pore size and distribution. Ni metal nanoparticles are uniformly deposited in the Al2O3 hollow fibers to prepare a Ni/Al2O3 catalyst and tested for the CO2 methanation reaction. Suitable reactor and catalyst loading methods are designed and optimized to achieve higher CO2 to methane conversion in a temperature range of 225 to 400 degrees C. The alpha-alumina phase, which is usually reported to be a poor support for Ni in CO2 methanation in the conventional fixed bed configuration, showed high activity when modulated as hollow fibers. Also, the selectivity to CH4 is enhanced and minimal CO formation is observed. The kinetic rate expressions are simulated for the prediction of methane and CO gas evolution at the outlet with temperature. The experimental results for the gas composition are in good agreement with the model predictions. The advantage of such a module reactor is explained based on the mass transfer limitations and consequently the reaction time constants arrived at from the predicted gas compositions.

Zinc-air batteries catalyzed using Co3O4 nanorod-supported N-doped entangled graphene for oxygen reduction reaction - Manna, Narugopal; Singh, Santosh K.; Kharabe, Geeta Pandurang; Torris, Arun; Kurungot, Sreekumar (ACS Applied Energy Materials, 2021)
The work reported here deals with the development of an efficient non-platinum electrocatalyst for electrochemical oxygen reduction reaction (ORR) through a sequential pathway involving hydrothermal treatment followed by freeze-drying to build the desired structural architecture of the catalyst. The designed catalyst (Co3O4/nitrogen-doped entangled porous 3D graphene (NEGF)), which contains Co3O4 nanorods anchored on the surface of three-dimensional (3D)-structured N-doped graphene, was found to display higher ORR activity during single-electrode testing and demonstrate a Zn-air battery (ZAB) system. Under the hydrothermal treatment at 180 degrees C, in the presence of ammonia, nitrogen was doped into the carbon framework of graphene, which subsequently formed a self-assembled entangled 3D structure of graphene after freeze-drying. The hydrothermal treatment and freeze-drying processes were found to play vital roles in tuning the morphological and structural features of the catalyst. The doped nitrogen, apart from its favorable contribution toward ORR, helped facilitate efficient dispersion of oxide nanorods on graphene. Co3O4/NEGF displayed remarkable ORR activity in 0.1 M KOH solution, as evident from the 60 mV onset potential shift compared to the state-of-the-art Pt/C catalyst and the Tafel slope value of 74 mV dec(-1) vs 68 mV dec(-1) for Pt/C. The ZAB fabricated by employing Co3O4/NEGF as the cathode catalyst was found to be an efficient competitor for the system based on the Pt/C cathode. This high performance has been credited to the controlled interplay of the governing factors such as the interfacial interactions leading to the efficient dispersion of metal oxide nanorods, increased catalyst surface area, the cooperative effect arising from the defects present in the N-doped porous 3D graphene, and the synergetic interactions operating in the system.
Keywords: cobalt-oxide nanorod; freeze-drying; hydrothermal; N-doped entangled graphene; oxygen reduction reaction; zinc-air battery

3D x-ray microtomography investigations on the bimodal porosity and high sulfur impregnation in 3D carbon foam for Li-S battery application - Thripuranthaka, M.; Chaturvedi, Vikash; Dwivedi, Pravin Kumari; Torris, Arun; Shelke, V. Manjusha (Journal of Physics-Energy, 2022)
Lithium-sulfur (Li-S) batteries, regarded as one of the most promising alternatives to current state-of-the-art rechargeable Li-ion battery technologies, have received tremendous attention as potential candidates for next-generation portable electronics and the rapidly advancing electric vehicle market. However, substantial capacity decay, miserable cycle life, and meagre stability remain critical challenges. More specifically, shuttling of polysulfide (Li2S (x) (3 < x <= 8)) species severely hinders the cycle performance resulting in capacity fade and cycling instability. In the present work, a highly conducting three-dimensional (3D) carbon nanofiber (CNF) foam has been synthesized using the lyophilization method followed by thermal pyrolysis. The highly porous foam materials have a bimodal porosity distribution in the nano and micro regime and were successfully investigated to serve as a potential host for sulfur species intended for Li-S battery application. 3D x-ray microtomography was employed to estimate the nature of sulfur impregnation and distribution in the 3D porous networks. On utilizing the final product as cathode material, sulfur impregnated carbonized CNF foam and modified the separator with functionalized multiwalled carbon nanotubes delivered a specific capacity of similar to 845 mAh g(-1) at 100 mA g(-1).
Keywords: bimodal porosity; CNF foam; Li-S battery; microtomography

Addressing challenges in sealing of scalable multifiber module for O-2 enrichment using LSCF membranes - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (International Journal of Applied Ceramic Technology, 2022)
Scalable and multifiber modules in oxygen separation face huge challenges due to difficulty in integrating all the necessary components, especially in sealing the fibers in a gas tight module. Here, we report our findings on design and fabrication of a multifiber La0.6Sr0.4Co0.2Fe0.8O3-delta (LSCF)-based module, which can be scaled up. The focus is on sealing ceramic-metal interfaces by layering of sealants of varying thermal properties. We have also incorporated the use of dead ended fibers to minimize ceramic-metal interfaces in the hot zones and present a new method for dead ending by flame melting. Pressurizing the air inlet feed from either bore side or shell side is detrimental to the structural integrity of the fibers. A thorough characterization of the fresh and spent fibers is also carried out using X-ray tomography and electron microscopy, which indicates effect of temperature and pressure on the fibers.
Keywords: Characterization; permeability; Perovskites

Air-cathode interface-engineered electrocatalyst for solid-state rechargeable zinc-air batteries - Manna, Narugopal; Singh, Santosh K.; Kurian, Maria; Torris, Arun; Kurungot, Sreekumar (ACS Applied Energy Materials, 2022)
Solid-state rechargeable zinc-air batteries (ZABs) are gaining interest as a class of portable clean energy technology due to their advantages such as high theoretical energy density, intrinsic safety, and low cost. It is expected that an appropriately triple-phase boundary (TPB) engineered, bifunctional oxygen reaction (OER and ORR) electrocatalyst at the air- electrode of ZABs can redefine the performance characteristics of these systems. To explore this possibility, an electrode material consisting of manganese- cobalt-based bimetallic spinel oxide (MnCo2O4)-supported nitrogen-doped entangled graphene (MnCo2O4/NEGF) with multiple active sites responsible for facilitating both OER and ORR has been prepared. The porous 3D graphitic support significantly affects the bifunctional oxygen reaction kinetics and helps the system display a remarkable catalytic performance. The air electrode consisting of the MnCo2O4/NEGF catalyst coated over the gas diffusion layer (GDL) ensures the effective TPB, and this feature works in favor of the rechargeable ZAB system under the charging and discharging modes. As an important structural and functional attribute of the electrocatalyst, the porosity and nitrogen doping in the 3D conducting support play a decisive aspect in controlling the surface wettability (hydrophilicity/hydrophobicity) of the air electrode. The fabricated solid-state rechargeable ZAB device with the developed electrode displayed a maximum peak power density of 202 mW cm(-2), which is significantly improved as compared to the one based on the Pt/C + RuO2 standard catalyst pair (124 mW cm(-2)). The solid-state device which displayed an initial charge-discharge voltage gap of only 0.7 V at 10 mA cm(-2) showed only a small increment of 86 mV after 50 h.
Keywords: air-cathode interface; bifunctional oxygen catalyst; N-doped entangled graphene; solid-state zinc-air battery; spinel oxides

Influence of ice templating on oxygen reduction catalytic activity of metal-free heteroatom-doped mesoporous carbon derived from polypyrrole for zinc-air batteries - Kurian, Maria; Ghosh, Meena; Vijayakumar, Vidyanand; Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Kurungot, Sreekumar (Energy Technology, 2022)
The development of highly active, cost-effective, and durable, noble metal-free oxygen reduction electrocatalysts is inevitable for the full-fledged implementation of fuel cells and zinc-air batteries. This work reports the synthesis of heteroatom (N, P, S)-doped metal-free mesoporous carbon-based electrocatalyst derived from polypyrrole by combining the ice templating, freeze-drying, and carbonization processes. The correlation between the structure and electrochemical activity of the polypyrrole-derived carbon-based electrocatalyst in the presence and absence of ice templating is investigated. The optimized electrocatalyst, aided by the ice-templating and freeze-drying step, shows an onset and half-wave potential (E-1/2) of 0.94 and 0.78 V vs reversible hydrogen electrode, respectively, in an alkaline electrolyte (0.1 m KOH). Later, the application of the optimized electrocatalyst is demonstrated in a primary zinc-air battery (ZAB) cell. The results prove that the ZAB device performance based on the homemade catalyst is on par with that of the state-of-the-art Pt/C cathode. The catalyst performance is correlated with the heteroatom doping and the enhanced porosity of the sample benefitted from ice templating. Ultimately, this work depicts a facile and rational synthesis of a truly metal-free electrocatalyst for the primary ZABs that can be a potential replacement for state-of-the-art systems.
Keywords: metal-free electrocatalysts; oxygen reduction reaction; zinc-air batteries

Study on anisotropy in wire arc additively manufactured Inconel 625 multi-layered wall and its correlation with molten pool thermal history - Nagallapati, Vishwanath; Choudhary, Amit; Torris, Arun; Muvvala, Gopinath; Dadasaheb, Sagar Pawar; Gudur, Srinath Ellaswamy (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
In the present study, the variation in molten pool thermal history with layer number during wire arc additive manufacturing of Inconel 625 wall was investigated. Further, its effect on the evolution of microstructure and anisotropy in mechanical and corrosion properties was reported. During the deposition process, the molten pool thermal history was monitored using a non-contact type IR pyrometer operating at 1.6 mu m wavelength. A total number of 40 layers were deposited, building a wall of 60 mm height. With an increase in layer number, the molten pool lifetime and cooling rate were found to increase and decrease, respectively, resulting in coarse grains and increased elemental segregation or Laves phase formation. To investigate its effect on mechanical properties, the samples were collected in a skewed fashion along the height with orientation in the deposition direction. The tensile specimens collected close to the substrate exhibited better strength and ductility, while the samples from the top location of the wall exhibited a relatively brittle mode of fracture, which was investigated by carrying out the fracture surface analysis using SEM. Corrosion test was also conducted along the height of the wall, wherein the samples close to substrate exhibited better corrosion resistance due to refined microstructure and low elemental segregations. Further, EDS, XRD analysis and hardness test were carried out to investigate the elemental composition, variation in phases and hardness with layer number, respectively.
Keywords: anisotropy; Layer number; mechanical properties; Molten pool thermal history; Wire arc additive manufacturing

Synthesis and characterization of partially biobased aromatic (Co)polycarbonates containing biphenylene units and pendant pentadecyl chains - Ichake, Amol B.; Nagane, Samadhan S.; Jadhav, Uday A.; Torris, Arun; Grau, Etienne; Cramail, Henri; Wadgaonkar, Prakash P. (Macromolecular Chemistry and Physics, 2022)
2-Pentadecyl-[1,1''-biphenyl]-4,4''-diol (PBD) is synthesized starting from cashew nut shell liquid-a by-product of cashew processing industry. A new series of partially biobased aromatic (co)polycarbonates possessing biphenylene units and pendant pentadecyl chains is synthesized by solution polycondensation of PBD or varying compositions of PBD and bisphenol-A with triphosgene in dry dichloromethane. Inherent viscosities and number average molecular weights of (co)polycarbonates are in the range 0.51-1.24 dL g(-1) and 18 x 10(3)- 43.4 x 10(3) g mol(-1), respectively indicating the formation of reasonably high molecular weight polymers. Flexible, transparent, and free-standing films of (co)polycarbonates can be cast from chloroform solution. (Co)polycarbonates are characterized using Fourier transform infrared spectroscopy (FTIR), H-1 NMR, C-13 NMR spectroscopy, X-ray diffraction (XRD), differential scanning calorimetry, and thermogravimetric analysis. T-10 and T-g values of (co)polycarbonates are in the range 417-433 and 8-147 degrees C, respectively. It is demonstrated that the T-g values can be tuned by incorporation of appropriate mol% of PBD as a comonomer in Bisphenol-A-based copolycarbonates. The lowering of the T-g values of (co)polycarbonates can be attributed primarily to the packing disruptive effect of flexible pentadecyl chains. Furthermore, the effect of incorporation of PBD as a comonomer on water contact angle values of (co)polycarbonates is evaluated.
Keywords: aromatic polycarbonates; biobased bisphenol; Cashew nut shell liquid; pentadecyl chain; Renewable resources

Trap inlaid cationic hybrid composite material for efficient segregation of toxic chemicals from water - Fajal, Sahel; Mandal, Writakshi; Mollick, Samraj; More, Yogeshwer D.; Torris, Arun; Saurabh, Satyam; Shirolkar, Mandar M.; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2022)
Metal-based oxoanions are potentially toxic pollutants that can cause serious water pollution. Therefore, the segregation of such species has recently received significant research attention. Even though several adsorbents have been employed for effective management of chemicals, their limited microporous nature along with non-monolithic applicability has thwarted their large-scale real-time application. Herein, we developed a unique anion exchangeable hybrid composite aerogel material (IPcomp-6), integrating a stable cationic metal-organic polyhedron with a hierarchically porous metal-organic gel. The composite scavenger demonstrated a highly selective and very fast segregation efficiency for various hazardous oxoanions such as, HAsO42-, SeO42-, ReO4-, CrO42-, MnO4-, in water, in the presence of 100-fold excess of other coexisting anions. The material was able to selectively eliminate trace HAsO42- even at low concentration to well below the As-v limit in drinking water defined by WHO.
Keywords: Aerogel; Chemical Separation; Hybrid composite; Metal-Organic Gel; Metal-Organic Polyhedra

Trap inlaid cationic hybrid composite material for efficient segregation of toxic chemicals from water (vol 61, e202203385, 2022) - Fajal, Sahel; Mandal, Writakshi; Mollick, Samraj; More, Yogeshwer D.; Torris, Arun; Saurabh, Satyam; Shirolkar, Mandar M.; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2022)

3D-printed polymer composite devices based on a ferroelectric chiral ammonium salt for high-performance piezoelectric energy harvesting - Sahoo, Supriya; Kothavade, Premkumar Anil; Naphade, Dipti R.; Torris, Arun; Praveenkumar, Balu; Zareba, Jan K.; Anthopoulos, Thomas D.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Materials Horizons, 2023)
Three-dimensional printing (3DP) is an emerging technology to fabricate complex architectures, necessary to realize state-of-the-art flexible and wearable electronic devices. In this regard, top-performing devices containing organic ferro- and piezoelectric compounds are desired to circumvent significant shortcomings of conventional piezoceramics, e.g. toxicity and high-temperature device processibility. Herein, we report on a 3D-printed composite of a chiral ferroelectric organic salt {[Me3CCH(Me)NH3][BF4]} (1) with a biodegradable polycaprolactone (PCL) polymer that serves as a highly efficient piezoelectric nanogenerator (PENG). The ferroelectric property of 1 originates from its polar tetragonal space group P4(2), verified by P-E loop measurements. The ferroelectric domain characteristics of 1 were further probed by piezoresponse force microscopy (PFM), which gave characteristic `butterfly' and hysteresis loops. The PFM amplitude vs. drive voltage measurements gave a relatively high magnitude of the converse piezoelectric coefficient for 1. PCL polymer composites with various weight percentages (wt%) of 1 were prepared and subjected to piezoelectric energy harvesting tests, which gave a maximum open-circuit voltage of 36.2 V and a power density of 48.1 mu W cm(-2) for the 10 wt% 1-PCL champion device. Furthermore, a gyroid-shaped 3D-printed 10 wt% 1-PCL composite was fabricated to test its practical utility, which gave an excellent output voltage of 41 V and a power density of 56.8 mu W cm(-2). These studies promise the potential of simple organic compounds for building PENG devices using advanced manufacturing technologies.

COF-supported zirconium oxyhydroxide as a versatile heterogeneous catalyst for Knoevenagel condensation and nerve agent hydrolysis - Shekhar, Pragalbh; Devulapalli, Venkata Swaroopa Datta; Reji, Reshma; Singh, Himan Dev; Jose, Aleena; Singh, Piyush; Torris, Arun; Vinod, Chatakudath P.; Tokarz III, John A.; Mahle, John J.; Peterson, Gregory W.; Borguet, Eric; et al. (iScience, 2023)
A composite of catalytic Lewis acidic zirconium oxyhydroxides (8 wt %) and a covalent organic framework (COF) was synthesized. X-ray diffraction and infrared (IR) spectroscopy reveal that COF's structure is pre-served after loading with zirconium oxyhydroxides. Electron microscopy confirms a homogeneous distri-bution of nano-to sub-micron-sized zirconium clusters in the COF. 3D X-ray tomography captures the micron-sized channels connecting the well-dispersed zirconium clusters on the COF. The crystalline ZrOx(OH)(y)@COF's nanostructure was model-optimized via simulated annealing methods. Using 0.8 mol % of the catalyst yielded a turnover number of 100-120 and a turnover frequency of 160-360 h(-1) for Knoevenagel condensation in aqueous medium. Additionally, 2.2 mol % of catalyst catalyzes the hy-drolysis of dimethyl nitrophenyl phosphate, a simulant of nerve agent Soman, with a conversion rate of 37% in 180 min. The hydrolytic detoxification of the live agent Soman is also achieved. Our study unveils COF-stabilized ZrOx(OH)(y) as a new class of zirconium-based Lewis + Bronsted-acid catalysts.

Double encapsulation of liquid active compounds using nanoclay reinforced polyurea microcapsules - Aher, Yogeshwar P.; Torris, Arun; Adhikari, Benu; Shukla, Ravi; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2023)
In recent years, there has been growing interest in the double encapsulation of drugs, agrochemicals, and fragrances, aiming to achieve the highest encapsulation efficiency and preserve the activity of the encapsulated core over an extended duration. However, when active ingredients in liquid form are double encapsulated, preventing the rupture of primary microcapsules during the second encapsulation process and the leakage of the encapsulated core are major challenges. This report describes a method that utilizes polyurea and starch for successful double encapsulation of dimethyl phthalate (DMP), a liquid insect-repellent, as a model active component. We demonstrate that the incorporation of 3 wt% montmorillonite (MMT) nanoclay strengthens the polyurea wall of the primary microcapsule and prevents its rupture during double encapsulation with starch. This process facilitates the uniform distribution of polyurea microcapsules within the starch matrix and significantly improves the mechanical integrity of the nanocomposite microcapsules embedded in starch. The double-encapsulated system developed in this study significantly reduces the release rate of encapsulated DMP.
Keywords: Controlled release; Double encapsulation; Microcapsules; Microencapsulation; Nanocomposites; Starch matrix

Functionalized CNT-azobenzene-PVA-based self-healing aqueous gel as a conductive photo-responsive actuator - Narayanan, Aswini; Bhagyasree, T. M.; Torris, Arun; Babu, Sukumaran Santhosh (Journal of materials chemistry C, 2023)
Conductive gels have gained attention from researchers owing to potential applications in flexible displays, implantable medical devices, touch panels, wearable electronic skin, sensors, soft robotics, etc. Photo-responsive conductance switching gels can make their way into various applications, including contact-free remote-controlled manipulation of the materials, implantable synthetic organs, and optical switches. Herein, we report an aqueous gel with boronic acid containing azobenzene crosslinker as the light-responsive part that can undergo reversible cis-trans isomerization on irradiation with UV-vis light and catechol functionalized single-walled carbon nanotube as a conductive part producing a self-healing aqueous gel with PVA. The 3D crosslinked gel network formed through the formation of boronic ester and hydrogen bonding between hydroxyl and boronic acid groups was confirmed using scanning electron microscopy, X-ray microtomography, and rheological experiments. Rheology results show that gel is a viscoelastic material with immediate self-healing properties. The presence of functionalized SWCNT in the gel matrix enhances the stability and results in a conductivity of up to 3.5 S cm-1 with a loading of 5 wt%. The gel network exhibits a photoresponsive conductance switching from 10 to 60 mu A with UV and visible light irradiation, respectively. The molecular level motions during the isomerization of azobenzene lead to macroscopic dynamic changes that can find applications in soft actuators. The photoresponsive conductivity switching and dynamic movements of the films make the present material suitable for contact-free switching applications. Responsive conductive gels have gained attention owing to potential applications in flexible displays, implantable medical devices, touch panels, wearable electronic skin, sensors, soft robotics, and related areas.
Keywords: Cyclodextrins; Supramolecular Hydrogels

Hierarchical covalent organic framework-foam for multi-enzyme tandem catalysis - Paul, Satyadip; Gupta, Mani; Dey, Kaushik; Mahato, Ashok Kumar; Bag, Saikat; Torris, Arun; Gowd, E. Bhoje; Sajid, Hasnain; Addicoat, Matthew A.; Datta, Supratim; Banerjee, Rahul (Chemical Science, 2023)
Covalent organic frameworks (COFs) are ideal host matrices for biomolecule immobilization and biocatalysis due to their high porosity, various functionalities, and structural robustness. However, the porosity of COFs is limited to the micropore dimension, which restricts the immobilization of enzymes with large volumes and obstructs substrate flow during enzyme catalysis. A hierarchical 3D nanostructure possessing micro-, meso-, and macroporosity could be a beneficial host matrix for such enzyme catalysis. In this study, we employed an in situ CO2 gas effervescence technique to induce disordered macropores in the ordered 2D COF nanostructure, synthesizing hierarchical TpAzo COF-foam. The resulting TpAzo foam matrix facilitates the immobilization of multiple enzymes with higher immobilization efficiency (approximately 1.5 to 4-fold) than the COF. The immobilized cellulolytic enzymes, namely beta-glucosidase (BGL), cellobiohydrolase (CBH), and endoglucanase (EG), remain active inside the TpAzo foam. The immobilized BGL exhibited activity in organic solvents and stability at room temperature (25 degrees C). The enzyme-immobilized TpAzo foam exhibited significant activity towards the hydrolysis of p-nitrophenyl-beta-d-glucopyranoside (BGL@TpAzo-foam: K-m and V-max = 23.5 +/- 3.5 mM and 497.7 +/- 28.0 mu M min(-1)) and carboxymethylcellulose (CBH@TpAzo-foam: K-m and V-max = 18.3 +/- 4.0 mg mL(-1) and 85.2 +/- 9.6 mu M min(-1) and EG@TpAzo-foam: K-m and V-max = 13.2 +/- 2.0 mg mL(-1) and 102.2 +/- 7.1 mu M min(-1)). Subsequently, the multi-enzyme immobilized TpAzo foams were utilized to perform a one-pot tandem conversion from carboxymethylcellulose (CMC) to glucose with high recyclability (10 cycles). This work opens up the possibility of synthesizing enzymes immobilized in TpAzo foam for tandem catalysis.

High rate, high temperature, dendrite free plating/stripping of Li in 3-dimensional honeycomb boron carbon nitride to realize an ultrastable lithium metal anode - Patrike, Apurva; Karbhal, Indrapal; Wasnik, Kundan; Torris, Arun; Maibam, Ashakiran; Krishnamurty, Sailaja; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Lithium (Li) metal could be the anode of choice for energy dense Li-batteries owing to its high theoretical specific capacity. However, low coulombic efficiency and poor safety on account of the occurrence of the Li-dendrites during charging-discharging pose a bottleneck for practical applications. In this work, we report a high-rate plating and stripping of Li through host engineering to realize ultrastable Li metal anode (LMA). Benchmark plating/stripping efficiency could be achieved via uniquely structured, highly ordered honeycomb boron carbon nitride (HBCN) as a functional scaffold. Boron and nitrogen doping, large surface area and ordered mesoporous structure induce homogeneous solid electrolyte interface (SEI) layer formation and provide numerous nucleation sites with subsequent dendrite-free growth with 99.98 % coulombic efficiency at 8 mA cm(-2) high current and 10 mAh cm(-2) capacity over 3000 cycles. Via post-cycling advanced characterizations techniques of Ex-situ XPS, 3D X-ray micro-tomography analyses and FESEM, we demonstrate the formation of a stable SEI layer and morphological changes that occurred during Li plating cycles in the HBCN structure. Computational studies validate the high lithium plating-stripping efficacy of HBCN to its highly ordered porous nature, exothermic Li-binding and upshift in the Fermi levels. When tested at elevated temperature (50 degrees C), a stable Li plating-stripping in HBCN is realised at 4 mA cm(-2) current and 10 mAh cm(-2) capacity values with similar to 100 % C.E. Furthermore, we report the results of testing a Li metal cell comprised of Li deposited HBCN anode and LiFePO4 (LFP) cathode.
Keywords: Boron carbon nitride; Dendrite-free Li metal anode; Functional scaffold; High temperature plating/stripping of Li; Molecular planarity parameter; X-ray micro-tomography

Luminescent 3D printed poly(lactic acid) nanocomposites with enhanced mechanical properties - Kothavade, Premkumar Anil; Yadav, Prashant; Nidhankar, Aakash D.; Torris, Arun; Pol, Harshawardhan; Kafi, Abdullah; Bateman, Stuart; Sukumaran, Santosh Babu; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2023)
The three-dimensional (3D) printing of functional composite materials has gained tremendous interest in recent years. Nevertheless, research on 3D printing of luminescent composite materials is very limited, and the mechanical properties of such 3D-printed composites are poor. Herein, we report the preparation and characterization of a poly(lactic acid) (PLA) composite that, when 3D printed, exhibits enhanced toughness and high solid-state fluorescence quantum yield. Incorporation of only 1 wt% pyrene butyric acid modified cellulose nanofibers (PBA-m-CNF) and l0 wt% thermoplastic polyurethane (TPU) into PLA led to 223% increase in toughness and 21% increase in tensile modulus of PLA. Scanning electron microscopy (SEM) and X-ray microcomputed tomography (mu-CT) analysis of the fractured cross-sections of 3D printed composites revealed a ductile failure mode. The PLA/PBA-m-CNF1/TPU10 3D printed composite also exhibited a high solid-state fluorescence quantum yield of 38.35%. To the best of our knowledge, this is the first report to show both enhanced mechanical properties and high solid-state fluorescence emission for 3D printable PLA. Such functional PLA composites could have potential applications in the fabrication of complex-shaped sensors, optical light pipes, etc.
Keywords: 3D printing; Composite; fluorescence; Nanocellulose; poly(lactic acid); toughness

Mitigating dendrite formation on a Zn electrode in aqueous zinc chloride by the competitive surface chemistry of an imidazole additive - Rana, Ashutosh; Thakare, Anup; Kumar, Nikhil; Mukherjee, Buddhadev; Torris, Arun; Das, Bidisa; Ogale, Satishchandra; Banerjee, Abhik (ACS Applied Materials and Interfaces, 2023)
Electrochemical energy storage systems are critical in several ways for a smooth transition from nonrenewable to renewable energy sources. Zn-based batteries are one of the promising alternatives to the existing state-of-the-art Li-ion battery technology, since Li-ion batteries pose significant drawbacks in terms of safety and cost-effectiveness. Zn (with a reduction potential of -0.76 V vs SHE) has a significantly higher theoretical volumetric capacity (5851 mAh/cm3) than Li (2061 mAh/cm3), and it is certainly far less expensive, safer, and more earth-abundant. The formation of dendrites, hydrogen evolution, and the formation of a ZnO passivation layer on the Zn anode are the primary challenges in the development and deployment of rechargeable zinc batteries. In this work, we examine the role of imidazole as an electrolyte additive in 2 M ZnCl2 to prevent dendrite formation during zinc electrodeposition via experimental (kinetics and imaging) and theoretical density functional theory (DFT) studies. To characterize the efficacy and to identify the appropriate concentration of imidazole, linear sweep voltammetry (LSV) and chronoamperometry (CA) are performed with in situ monitoring of the electrodeposited zinc. The addition of 0.025 wt % imidazole to 2 M ZnCl2 increases the cycle life of Zn-symmetric cells cycled at 1 mA/cm2 for 60 min of plating and stripping dramatically from 90 to 240 h. A higher value of the nucleation overpotential is noted in the presence of imidazole, which suggests that imidazole is adsorbed at a competitively faster rate on the surface of zinc, thereby suppressing the zinc electrodeposition kinetics and the formation. X-ray tomography reveals that a short circuit caused by dendrite formation is the main plausible failure mechanism of Zn symmetric cells. It is observed that the electrodeposition of zinc is more homogeneous in the presence of imidazole, and its presence in the electrolyte also inhibits the production of a passivating coating (ZnO) on the Zn surface, thereby preventing corrosion. DFT calculations conform well with the stated experimental observations.
Keywords: dendrite; Density functional theory; exchange current density; Imidazole; X-ray computed tomography; zinc metal electrodeposition

Advanced 3D network of N-doped graphitic carbon with FeNi alloy embedding for high-performance rechargeable Zn-air batteries - Pandikassala, Ajmal; Kurian, Maria; Gangadharan, Pranav K.; Torris, Arun; Kurungot, Sreekumar (Advanced Sustainable Systems, 2024)
Despite the significant progress in Zn-air batteries (ZABs), their widespread use in the rechargeable sector is hindered due to the scarcity of efficient bifunctional oxygen catalysts that can catalyze both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER). To address this, an ORR/OER bifunctional electrocatalyst is designed with ultrafine alloyed FeNi nanoparticles encapsulated in a 3D interconnected N- doped carbon network structure, featuring a carbon nitride backbone enclosed in graphitic carbon. The FeNi electrocatalyst (3DFeNiPDC) showed good bifunctional activity toward both ORR and OER in the basic medium with a low overpotential value of 30 mV for ORR and 6 mV for OER compared to its state-of-the-art counterparts Pt/C, and RuO2, respectively. Utilizing 3DFeNiPDC in a rechargeable Zn-air battery (RZAB) yields an open circuit voltage (OCV) of 1.35 V, a maximum power density of 232 mW cm-2, and an energy density of 707 W h kg-1. Additionally, a flexible RZAB employing 3DFeNiPDC demonstrates an OCV of 1.4 V with various bending angles. These finding suggest 3DFeNiPDC as a viable alternative to noble metal-based RZABs, offering superior bifunctional electrocatalytic activity and stability, particularly with its enhanced air-breathing properties facilitating improved operability under practical conditions. The bifunctional electrocatalytic activity of FeNi alloy nanoparticles embedded in a 3D- interconnected N-doped graphitic carbon (3DFeNiPDC) for both oxygen reduction and oxygen evolution is studied. The 3D architecture and core-shell characteristics of FeNi alloy nanoparticles provide better activity and stability for oxygen electrocatalysis. The electrocatalytic activity of 3DFeNiPDC has been exploited for liquid-state and solid-state flexible rechargeable zinc-air batteries. image
Keywords: Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable flexible zinc-air battery

Biobased reusable nonisocyanate polyurethane hot-melt adhesives with potential chemical degradability - Ghuge, Gorakh Hiraman; Torris, Arun; Nair, Kiran Sukumaran (ACS Applied Polymer Materials, 2024)
Hot-melt adhesives (HMAs) derived from renewable resources are always attractive, as they promote less dependence on fossil resources and aid in developing environmentally friendly materials. However, developing sustainable HMAs exhibiting good adhesive performance and biodegradability remains challenging. Herein, reusable biobased HMAs with a high bio content of 88-90%, biodegradability, and tunable adhesive nature were developed as a possible alternative to conventional petroleum-based hot-melt adhesives. Moreover, the structure-property relationship of the product was investigated in detail. By tailoring the monomer composition, NIPU-40 HMA exhibited a good bonding ability with a superior adhesion strength of 6.39 MPa. To the best of our knowledge, this is the highest adhesion strength observed when bonding with an Al substrate among the biobased thermoplastic NIPU-HMAs. Impressively, NIPU-HMAs could display excellent reusability even after three bonding and debonding cycles without a significant drop in the adhesive strength and were found to exhibit good adhesion performance under wet conditions. More importantly, the NIPU-HMAs are prone to degradation under acid-catalyzed conditions. Considering their features, these biobased NIPU thermoplastic hot-melt adhesives offer an opportunity to create environmentally friendly, degradable adhesives that possess excellent adhesive strength and can be reused multiple times.
Keywords: acid degradability; biobased NIPUs; cyclic carbonates; hot meltadhesives; lap shearstrength; spiro-aromatic

Biodegradable and 3D printable lysine functionalized polycaprolactone scaffolds for tissue engineering applications - Naik, Sonali S.; Torris, Arun; Choudhury, Namita R.; Dutta, Naba K.; Nair, Kiran Sukumaran (Biomaterials Advances, 2024)
Tissue engineering (TE) has sparked interest in creating scaffolds with customizable properties and functional bioactive sites. However, due to limitations in medical practices and manufacturing technologies, it is challenging to replicate complex porous frameworks with appropriate architectures and bioactivity in vitro. To address these challenges, herein, we present a green approach that involves the amino acid (L-lysine) initiated polymerization of epsilon-caprolactone (CL) to produce modified polycaprolactone (PCL) with favorable active sites for TE applications. Further, to better understand the effect of morphology and porosity on cell attachment and proliferation, scaffolds of different geometries with uniform and interconnected pores are designed and fabricated, and their properties are evaluated in comparison with commercial PCL. The scaffold morphology and complex internal micro-architecture are imaged by micro-computed tomography (micro-CT), revealing pore size in the range of similar to 300-900 mu m and porosity ranging from 30 to 70 %, while based on the geometry of scaffolds the compressive strength varied from 143 +/- 19 to 214 +/- 10 MPa. Additionally, the degradation profiles of fabricated scaffolds are found to be influenced by both the chemical nature and product design, where Lys-PCL-based scaffolds with better porosity and lower crystallinity degraded faster than commercial PCL scaffolds. According to in vitro studies, Lys-PCL scaffolds have produced an environment that is better for cell adhesion and proliferation. Moreover, the scaffold design affects the way cells interact; Lys-PCL with zigzag geometry has demonstrated superior in vitro vitality (>90 %) and proliferation in comparison to other designs. This study emphasizes the importance of enhancing bioactivity while meeting morphology and porosity requirements in the design of scaffolds for tissue engineering applications.
Keywords: Additive manufacturing; Amino acid; Micro-computed tomography; Polycaprolactone

Cathode|electrolyte interface engineering by a hydrogel polymer electrolyte for a 3D porous high-voltage cathode material in a quasi-solid-state zinc metal battery by in situ polymerization - Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Dilwale, Swati; Kanheerampockil, Fayis; Kurungot, Sreekumar (SMALL, 2024)
This work highlights the development of a superior cathode|electrolyte interface for the quasi solid-state rechargeable zinc metal battery (QSS-RZMB) by a novel hydrogel polymer electrolyte using an ultraviolet (UV) light-assisted in situ polymerization strategy. By integrating the cathode with a thin layer of the hydrogel polymer electrolyte, this technique produces an integrated interface that ensures quick Zn2+ ion conduction. The coexistence of nanowires for direct electron routes and the enhanced electrolyte ion infiltration and diffusion by the 3D porous flower structure with a wide open surface of the Zn-MnO electrode complements the interface formation during the in situ polymerization process. The QSS-RZMB configured with an integrated cathode (i-Zn-MnO) and the hydrogel polymer electrolyte (PHPZ-30) as the separator yields a comparable specific energy density of 214.14 Wh kg(-1) with that of its liquid counterpart (240.38 Wh kg(-1), 0.5 M Zn(CF3SO3)(2) aqueous electrolyte). Other noteworthy features of the presented QSS-RZMB system include its superior cycle life of over 1000 charge-discharge cycles and 85% capacity retention with 99% coulombic efficiency at the current density of 1.0 A g(-1), compared to only 60% capacity retention over 500 charge-discharge cycles displayed by the liquid-state system under the same operating conditions.
Keywords: cathode-electrolyte interface tuning; dendrite inhibition; epitaxial zinc deposition; hydrogel polymer electrolyte; In situ polymerization; Quasi solidstate rechargeable zinc metal battery

Nanotrap infused ultrathin hybrid composite material for rapid and highly selective entrapment of 99TcO4- - Mandal, Writakshi; Fajal, Sahel; Majumder, Dipanjan; Sengupta, Arijit; Let, Sumanta; Urkude, Rajashri R.; Shirolkar, Mandar M.; Torris, Arun; Ghosh, Sujit K. (CHEMICAL SCIENCE, 2024)
Keywords: Adsorption; CAPTURE; EFFICIENT; Metal-organic framework; Removal; TECHNETIUM

Ultralight crystalline hybrid composite material for highly efficient sequestration of radioiodine - Fajal, Sahel; Mandal, Writakshi; Torris, Arun; Majumder, Dipanjan; Let, Sumanta; Sen, Arunabha; Kanheerampockil, Fayis; Shirolkar, Mandar M.; Ghosh, Sujit K. (Nature Communications, 2024)
Considering the importance of sustainable nuclear energy, effective management of radioactive nuclear waste, such as sequestration of radioiodine has inflicted a significant research attention in recent years. Despite the fact that materials have been reported for the adsorption of iodine, development of effective adsorbent with significantly improved segregation properties for widespread practical applications still remain exceedingly difficult due to lack of proper design strategies. Herein, utilizing unique hybridization synthetic strategy, a composite crystalline aerogel material has been fabricated by covalent stepping of an amino-functionalized stable cationic discrete metal-organic polyhedra with dual-pore containing imine-functionalized covalent organic framework. The ultralight hybrid composite exhibits large surface area with hierarchical macro-micro porosity and multifunctional binding sites, which collectively interact with iodine. The developed nano-adsorbent demonstrate ultrahigh vapor and aqueous-phase iodine adsorption capacities of 9.98 g.g-1 and 4.74 g.g-1, respectively, in static conditions with fast adsorption kinetics, high retention efficiency, reusability and recovery. The development of effective adsorbents of radioiodine nuclear waste remains difficult due to the lack of proper material design strategies. Here the authors report an ultralight hierarchically porous crystalline multifunctional hybrid nanocomposite for ultrafast entrapment of iodine and polyiodide species under both static and dynamic condition.

Wide temperature enhanced sodium storage in tailored, sustainable sodiophilic biphasic N-doped carbon - Yadav, Poonam; Das, Anoushka K.; Torris, Arun; Wasnik, Kundan; Koppisetti, Heramba Venkata Sai Rama Murthy; Pol, Vilas G.; Shelke, Vilas; Shelke, Manjusha (Materials Today Chemistry, 2024)
Alternative to Li-ion batteries(LIB), Na-ion batteries (NIB) and Na metal batteries (NMB) are gaining significant attention due to their low cost, abundance, and safety. By modulating microstructural properties such as graphitization, heteroatom doping, surface-rich functional groups, and interlayer d-spacing, Na-ion storage in NIB and Na plating/striping in NMB can be ameliorated. This study reports sodiophilic N-doped polymer-derived carbon (PDC) as an anode for NIB and host for Na metal in NMB. As NIB anode, PDC provides a storage capacity of 173 mAh g- 1 at 1 A g- 1 in half-cell and 84 mAh g- 1 at 1C (1C = 128 mAhg- 1) in full-cell with Na3V2(PO4)2F3 (NVPF) cathode. As Na metal anode (NMA) host, a high columbic efficiency (C.E.) of 99.45% for over 1000 cycles at 6 mA cm- 2_4 mAh cm-2 is obtained. Furthermore, fascinating wide temperature (50 degrees C and -20 degrees C) sodiumion storage is successfully demonstrated by PDC. Advanced X-ray photoelectron spectroscopy (XPS) confirmed the formation of stable and uniform solid electrolyte interphase (SEI) composed of inorganic and organic components, X-ray microtomography confirmed uniform Na plating throughout the volume of the electrode analogous to Brunauer-Emmett-Teller (BET) surface area, Raman spectroscopy, X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) results. A sustainable and scalable promising biphasic NIB anode and sodiophilic host for Na metal was possible due to larger d-spacing, partial graphitization, high mesoporosity, N-doping, presence of surface functional groups, better charge transfer, and diffusion properties.
Keywords: Full-cell; Low and elevated temperatures; Na metal host; Polymer-derived carbon; Sodium-ion battery; X-ray tomography

Anode|electrolyte|cathode interface engineering to develop a robust zinc metal hydrogel battery - Dilwale, Swati; Babu, Athira; Kanheerampockil, Fayis; Torris, Arun; Puthiyaveetil, Priyanka Pandinhare; Bhat, Suresh; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
The poor electrode-electrolyte interfaces in quasi-solid-state zinc metal batteries often hinder Zn2+ ion transport due to the poor compatibility of the gel electrolyte with the electrodes. This report proposes a dual-interface engineering strategy across the anode, cathode, and separator using a single hydrogel polymer electrolyte (HPE). The integration of vanadyl phosphate functionalized carbon nanotubes (VP/fCNT) into a commercial glass fiber (GF) separator, followed by a thin hydrogel coating and UV-light photopolymerization, resulted in a dual-interface engineered cathode-separator-electrolyte structure (VP/IC-EGF). To mitigate the dendritic growth, an artificial solid electrolyte interface was developed on Zn foil (AEI@Zn). The engineered GF (EGF) demonstrates a room-temperature conductivity of 6.5 mS cm-1 and a high electrochemical stability window of 2.4 V vs. Zn|Zn2+. The symmetric cell with AEI@Zn|EGF|AEI@Zn exhibits exceptional plating/stripping stability over 1400 h at a current density of 0.1 mA cm-2 and a capacity of 0.1 mAh cm-2. Moreover, the low-volume cell (AEI@Zn & Vert;VP/IC-EGF), featuring the dual-interface-engineered cathode-separator-electrolyte, demonstrates outstanding cycling stability with over 3000 charge-discharge cycles at a current rate of 1.0 A g-1, retaining 98-99% of its initial capacity and showing high coulombic efficiency. These findings underscore the significant impact of interface engineering on enhancing the performance of ZMBs.

Binder-free in situ interface reconstruction of NiMoO4 nanorods over Ni(OH)2 nanosheets for efficient urea oxidation - Kumar, Yogesh; Barik, Sidharth; Kharabe, Geeta Pandurang; Torris, Arun; Singh, Mayank U.; Mohan, S.; Galave, Chaitanya; Tekawadia, Jyoti; Kanawade, Rajesh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
Replacing the energy-intensive oxygen evolution reaction (OER) with the urea oxidation reaction (UOR) in electrochemical water splitting offers simultaneous green hydrogen production and urea-rich wastewater oxidation, enhancing energy efficiency and economic viability. In this study, a non-noble metal-based binder-free NiMoO4/Ni(OH)2/NF electrocatalyst is developed, featuring NiMoO4 nanorods anchored on Ni(OH)2 nanosheets. This unique morphology facilitates a highly active in situ reconstructed interface, delivering a current density of 134 mA cm-2 at 1.40 V (vs RHE) in 1 m KOH with 0.33 m urea, significantly outperforming its individual components. The catalyst demonstrates excellent stability over 50 h at 30 mA cm-2. When integrated into an anion exchange membrane urea electrolyser (13 cm2 area) with Pt@C/NF as the HER cathode, the system achieves 192 mA cm-2 at 1.60 V. The post-UOR studies confirm the presence of an amorphous NiMoO4-crystalline Ni(OH)2 interface, which plays a key role in enhancing the availability of the active sites to enhance the UOR performance. The improved electrochemical performance of the engineered catalyst can be ascribed to the in situ reconstructed amorphous-crystalline interface, optimal hydrophilicity, reduced charge transfer resistance, and the distinct morphology. This strategy offers a promising pathway for developing highly active electrocatalysts for energy conversion applications.
Keywords: AEM; electrolyser; OWS; tomography; UOR; wastewater

Bioinspired nanochitin-based porous constructs for light-driven whole-cell biotransformations - Arumughan, Vishnu; Medipally, Hitesh; Torris, Arun; Leva, Tuukka; Grimm, Hanna C.; Tammelin, Tekla; Kourist, Robert; Kontturi, Eero (Advanced Materials, 2025)
Solid-state photosynthetic cell factories (SSPCFs) are a new production concept that leverages the innate photosynthetic abilities of microbes to drive the production of valuable chemicals. It addresses practical challenges such as high energy and water demand and improper light distribution associated with suspension-based culturing; however, these systems often face significant challenges related to mass transfer. The approach focuses on overcoming these limitations by carefully engineering the microstructure of the immobilization matrix through freeze-induced assembly of nanochitin building blocks. The use of nanochitins with optimized size distribution enabled the formation of macropores with lamellar spatial organization, which significantly improves light transmittance and distribution, crucial for maximizing the efficiency of photosynthetic reactions. The biomimetic crosslinking strategy, leveraging specific interactions between polyphosphate anions and primary amine groups featured on chitin fibers, produced mechanically robust and wet-resilient cryogels that maintained their functionality under operational conditions. Various model biotransformation reactions leading to value-added chemicals are performed in chitin-based matrix. It demonstrates superior or comparable performance to existing state-of-the-art matrices and suspension-based systems. The findings suggest that chitin-based cryogel approach holds significant promise for advancing the development of solid-state photosynthetic cell factories, offering a scalable solution to improve the efficiency and productivity of light-driven biotransformation.
Keywords: biocatalysis; light-driven biotransformation; nanochitins; porous materials

Defect-rich CoFe-alloy with engineered carbon support for high-performance rechargeable Zn-air batteries - Kharabe, Geeta Pandurang; Barik, Sidharth; Torris, Arun; Maria, Anit; Kumar, Yogesh; Kurungot, Sreekumar (Small, 2025)
Defect-rich CoFe-alloy with engineered carbon support is synthesized as a bifunctional cathode, coupled with a modified electrode fabrication technique, for rechargeable zinc-air batteries (RZABs). The CoFe(2:1)/N-rGCNT-catalyst is synthesized by annealing graphene oxide (GO), cobalt and iron acetate, and melamine, leading to the in situ formation of CoFe alloy-encapsulated CNTs. This resulted in a unique layer-separated Fe-rich skin@CoFe alloy decorated nitrogen-doped graphene (NGr) with CoFe-encapsulated CNTs. The interplay of line defects, enhanced conductivity, and electronic modulation underpins electrocatalyst's performance. Electrochemical analysis revealed an onset potential of 955 mV vs RHE, a half-wave potential of 835 mV vs RHE for oxygen reduction reaction (ORR) and an overpotential of 340 mV for oxygen evolution reaction (OER), yielding a Delta E of 0.73 V, comparable to the reported catalysts. The 3D X-ray microtomography simulations suggest improved air permeability of CoFe(2:1)/N-rGCNT facilitates easier gas diffusion, contributing in better device performance. The RZAB with CoFe(2:1)/N-rGCNT-cathode exhibited a peak power density of 171.3 mW cm(-)2, surpassing 140.8 mW cm(-)2 obtained from a cell based on Pt/C-cathode. The Co/N-rGCNT-based battery achieved a stable discharge profile at 10 mA cm(-)2 with a specific capacity of 650 mAh g(-)(1)Zn, and in rechargeable mode, achieved 140 h of high-rate charge-discharge cycling capability.
Keywords: 3D tomography; N-doping; alloy encapsulated structure; device demonstration; grain boundaries; oxygen reduction and evolution reactions; rechargeable zinc-air battery

Nano-springe enriched hierarchical porous MOP/COF hybrid aerogel: efficient recovery of gold from electronic waste - Majumder, Dipanjan; Fajal, Sahel; Shirolkar, Mandar M.; Torris, Arun; Banyla, Yashasvi; Biswas, Kishalay; Rasaily, Sagarmani; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2025)
Extraction of gold from secondary resources such as electronic waste (e-waste) has become crucial in recent times to compensate for the gradual scarcity of the noble metal in natural mines. However, designing and synthesizing a suitable material for highly efficient gold recovery is still a great challenge. Herein, we have strategically designed rapid fabrication of an ionic crystalline hybrid aerogel by covalent threading of an amino-functionalized metal-organic polyhedra with an imine-linked chemically stable covalent organic framework at ambient condition. The hierarchically porous ultra-light aerogel featuring imine-rich backbone, high surface area, and cationic sites have shown fast removal, high uptake capacity (2349 mg/g), and excellent selectivity towards gold sequestration. Besides, the aerogel can extract ultra-trace gold-ions from different terrestrial water bodies, aiming towards safe drinking water. This study demonstrates the great potential of the composite materials based on a novel approach to designing a hybrid porous material for efficient gold recovery from complex water matrices.
Keywords: Aerogel; COF; E-waste; Gold; MOP

Thrombin immobilized hemocompatible radiopaque polyurethane microspheres for topical blood coagulation - Naik, Sonali S.; Torris, Arun; Ghuge, Gorakh Hiraman; Karthika, V. K.; Joseph, Roy; Nair, Kiran Sukumaran (JOURNAL OF BIOMEDICAL MATERIALS RESEARCH PART A, 2025)
Keywords: ALGINATE MICROSPHERES; ENDOVASCULAR TREATMENT; PRECISE LOCALIZATION

Understanding the structural characteristics of modified ceramic hollow fiber oxygen transport membranes through in silico tomography simulation study - Jogdand, Shunottara M.; Sharma, Jyoti; Khilari, Rushikesh S.; Mahajan, Digvijay P.; Patil, Prashant; Pol, Harshavardhan V.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2025)
Design and development of integrated membrane reactor systems are gaining attention as a sustainable solution capable of performing multiple functions in a single reactor. Membrane reactors made of mixed ionic-electronic conduction materials dosing pure O to the reactions can be exploited for various catalytic processes. In this case, micro- and macrostructures of the membrane surface play a significant role in the permeation performance of membranes, and understanding these parameters prior to scaling up to modules is imperative. Here, 3D X-ray tomography imaging, a versatile nondestructive instrumental technique, is used in understanding the structural behavior of the membrane walls at different structural alignments, leading to anticipation of fouling areas upon assembling membrane reactors. La0.6Sr0.4Co0.2Fe0.8O3-delta hollow fiber membranes are fabricated by the phase inversion method and further modified by the optimized acid etching technique. In silico simulations on different morphologies before and after surface modifications are carried out under varying flow rates at nonambient temperatures to mimic real experimental conditions. Critical parameters such as gas velocity, pressure exerted on cavity walls, and strain, dictating structural integrity of the fibers under experimental conditions, were evaluated. As a result of the assessment, the surface-modified structural morphology with finger-like cavities initiating from the inner wall of the membrane was found to be robust. Increase in the pore size, nonuniform pore size distribution, and irregular and interdigitated cavities formed in outer fingered membranes after multiple surface treatments led to an similar to 5 fold increase in the average pressure exerted at the cavity walls when compared to inner fingered membranes. Strain profile generated for inner fingered membranes shows homogeneous distribution of strain for the applied stress throughout the 3D geometry of the membrane. This detailed structural analysis of the membrane will help in building a more robust and efficient system for scale-up applications.
Keywords: 3D X-ray tomography; in silico simulation; oxygen transport membranes; perovskite; phase inversionmethod

Design, synthesis, and adhesive performance evaluation of DOPA-Functionalized polyurethane elastomers - Davis, Disiya; Alam, Md Shafi; Purushothaman Bindu, Bhadra; Lakshmi, Durga; N Muhammed, Hasin; Torris, Arun; Ambade, Ashootosh V.; Sukumaran Nair, Kiran (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2026)
Functional polyurethane (PU) hot-melt adhesives were developed through the incorporation of a dopamine-derived chain extender (DADO) into thermoplastic PUs. The DADO monomer was synthesized via a four-step route and successfully integrated into the PU backbone using a one-pot, two-step polymerization involving polycaprolactone-diol and 4,4 `-methylenebis(phenyl isocyanate). Spectral analyses confirmed the formation of urethane linkages and the effective incorporation of catechol moieties. Monomodal molecular weight distributions were obtained through size-exclusion chromatography with Mn ranging from 12,000 to 17,000 g/mol. Thermal analyses demonstrated two-step decomposition behavior and a progressive increase in glass transition temperature with increasing DADO content. Mechanical testing revealed that there was substantial improvement in the tensile strength of these materials from 1.34 MPa for unmodified PU (PU-0) to 14.3 MPa for PU-10. Adhesion performance exhibited a similar trend, with PU-10 attaining the highest lap-shear strength of 3.92 +/- 0.19 MPa on the Al substrate. PU-10 exhibited the highest lap-shear strength of 3.92 +/- 0.19 MPa on aluminum and superior underwater stability with a value of 2.78 +/- 0.47 MPa compared to other formulations. Overall, controlled incorporation of DADO significantly enhances properties, and PU-10 represents the optimal formulation for high-performance hot-melt PU adhesives.
Keywords: chain extender; dopamine; hot-melt adhesive; polycaprolactone diol; polyurethanes

Dynamic janus hydrogen bond mimicry unlocks tough, flexible supramolecular elastomers for strain sensing - Lakshmi, Durga; Wagh, Mahendra A.; Sharma, Aakash; Alam, Md Shafi; Selvan, T. Muthamil; Torris, Arun; Mondal, Titash; Sanjayan, Gangadhar J.; Nair, Kiran Sukumaran (Chemistry of Materials, 2026)
Flexible and wearable electronics demand stretchable sensors with polymer elastomers as key matrixes for mechanical flexibility and durability. However, despite their excellent elasticity, their limited mechanical strength remains a challenge. To address this limitation, in this study, we report the rational design of supramolecular polyurethane elastomers (SPUs) incorporating nucleobase-inspired aminopyrimidinedione with DDA-AAD (G-C mimic) reversible triple hydrogen bonds. This dual-domain architecture gives rise to a durable supramolecular network with enhanced mechanical properties, yielding elastomers that are soft, stretchable, and tough. By tuning of the density of dynamic cross-links, mechanical properties were systematically modulated. SPU-0.5 exhibited a maximum tensile strength of 16.14 MPa, representing a 67-fold strength enhancement over that of SPU-0. Although increasing the aminopyrimidinedione (APD) content reduced elongation, SPU-0.2 retained a high elongation of 1060% and showed the lowest residual strain during cyclic tests. To be of great interest, the activation energy increased with increasing hydrogen bonding content up to SPU-0.1, whereas beyond SPU-0.2 it decreased, likely due to extensive hydrogen bond formation. Furthermore, SPU-0.2-SP, a conductive variant, demonstrated a promising strain-sensing performance even after hundreds of cycles. Overall, the insights gained from this study advance the development of intelligent soft materials and lay the groundwork for next-generation flexible and wearable electronic devices.

Fast self-healing in a layered molecular crystal mediated by stress-induced symmetry breaking - Ghosh, Ishita; Biswas, Rabindra; Tanwar, Manushree; Bhunia, Surojit; Das, Kaustav; Torris, Arun; Mondal, Amit; Raghunathan, Varun; Kumar, Rajesh; Reddy, C. Malla (Nature Communications, 2026)
In recent years, symmetry-breaking has emerged as a powerful tool for significantly altering various physical properties in 2D layered materials. However, the breaking of symmetry by means of mechanical stress in organic crystals remains elusive. Here, we demonstrate a simple approach to engineer symmetry-breaking through mechanical stress fields in a layered molecular crystal, resulting in autonomous and fast self-healing under ambient temperature and pressure conditions. Fracture mechanics analysis reveals that the crystal adheres to an elasto-plastic model, with formation of a plastic zone at the crack tip, which prevents further crack propagation, facilitating the self-healing process. Spatially resolved Raman mapping reveals that the crack formation is accompanied by a distinct symmetry-breaking mechanism at the microstructural level. A six-fold increase in non-linear second harmonic (SH) activity, triggered by mechanical perturbation, further validates the local symmetry breaking in an otherwise centrosymmetric crystal. Furthermore, symmetry is restored following successful healing, as evidenced by the disappearance of the SH signal in the healed regions. This study not only broadens the scope of self-healing mechanisms viable in molecular materials but also offers key insights into the role of symmetry breaking and its potential for related technological applications.

High-performance sultone-modified PVA/PAMPS semi-IPN hydrogels for proton exchange membranes - Patwadkar, Manjusha V.; Illathvalappil, Rajith; Torris, Arun; Francis, Sifa C.; Kurungot, Sreekumar; Badiger, Manohar V. (Journal of Applied Polymer Science, 2026)
Hydrogel membranes composed of poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) and sultone-modified poly(vinyl alcohol) (PVA) were successfully synthesized and evaluated as promising proton-conducting materials. A key advantage involves the premodification of PVA with 1,3-propane sultone to introduce sulfonic acid groups, thereby imparting proton conductivity to the PVA backbone. This sultone-modified PVA was then physically entangled within a PAMPS cross-linked network to form novel semi-interpenetrating network (semi-IPN) hydrogels. This synergistic design leverages the excellent film-forming and mechanical properties of PVA with the high proton conductivity inherent to PAMPS. The synthesized membranes exhibited robust mechanical properties, with tensile strengths ranging from 5 to 30 MPa and percentage elongations between 200% and 400%, depending on their humidity content. These hydrogel membranes demonstrated proton conductivities ranging from 0.6 to 4.3 x 10-2 S cm-1. The activation energy for proton conduction was found to be as low as 3.5 kJ mol-1, significantly lower than that of the commercial benchmark membrane, Nafion 117 (12 kJ mol-1). These findings underscore the potential of these novel PAMPS/sultone-modified PVA semi-IPN hydrogel membranes for advanced fuel cell applications.
Keywords: batteries and fuel cells; functionalization of polymers; Gels; membranes; polyelectrolytes

Insight Into the Influence of Salinity on Flow and Flocculation Behavior of Acrylamide-Based Cationic Polyelectrolyte - Ranganath, Suresha P.; Kurian, Rachna; Torris, Arun; Khairnar, Ajay; Ravindranathan, Sapna; Rajamohanan, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (Journal of Applied Polymer Science, 2026)
The viscometric behavior of aqueous solutions of acrylamide and acrylamidopropyl trimethylammonium chloride copolymers (AM-co-APTMAC) with varying cationic content under different salinity conditions was studied. Viscometric measurements were employed to determine intrinsic viscosity and quantify the influence of electrostatic interactions on chain conformation. Rheology experiments were performed to probe dynamic flow behavior under shear to obtain insights into polyelectrolyte viscoelastic properties under conditions mimicking industrial processes. Viscometric and rheology data analysis is augmented with insights from NMR relaxation and pulsed field gradient NMR diffusion experiments. Further, flocculation of kaolin suspensions was studied using aqueous solutions of AM-co-APTMAC copolymers with different charge fractions in the presence and absence of salt. The physicochemical insights on the behavior of AM-co-APTMAC polyelectrolytes in solution from this study could be relevant in practical applications, such as plants that use seawater or in cases where the ionic strength of suspensions is high due to salinity in the medium.
Keywords: copolymers; polyelectrolytes; structure property relationships; theory and modeling

Self-healing hydrogel electrolyte enabled by dynamic polar covalent and noncovalent interactions for high-performance rechargeable zinc-metal batteries: a leap toward sustainable energy storage - Puthiyaveetil, Priyanka Pandinhare; Kurian, Rachna Maria; Samudre, Nikhil S.; Balasubramanian, Rajalakshmi; Torris, Arun; Pockil, Fayis Kanheeram; Bhat, Suresh; Ajithkumar, T. G.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Advanced Energy Materials, 2026)
Hydrogel polymer electrolytes with superior multifunctional properties are promising alternatives to aqueous electrolytes for resolving interfacial issues in rechargeable zinc-metal batteries. In this study, an intrinsic self-healing hydrogel polymer electrolyte (PHBC-4) is synthesized, engineered through an integrated approach involving the polar covalent (B & horbar;O bond), hydrogen-bond (polyvinyl alcohol-hydroxypropyl methylcellulose interface), and coordination-type (Zn & horbar;O) interactions to enable self-healing functionality. The PHBC-4 has demonstrated high ionic conductivity (4.6 x 10-2 S cm-1), good oxidative stability (2.3 V vs Zn|Zn2+), a high cation transference number (0.89), superior tensile strength (0.32 MPa), and an impressive healing efficiency of 93% achieved just within 5 min, confirming its robust self-healing capability. In Zn||Zn symmetric cells, it effectively suppresses dendrite growth, ensuring stable cycling for over 1032 h with an areal capacity of 1.0 mAh cm-2 at a current density of 1.0 mA cm-2. When paired with a Zn-doped MnO cathode in the rechargeable homemade pouch cell, the system delivers a high specific capacity of 160 mAh g-1 at 0.10 A g-1 and cycling stability up to 493 charge-discharge cycles at 2.0 A g-1. The self-healing ability of PHBC-4 HGPE is confirmed in a homemade pouch cell via OCV and charge-discharge tests, demonstrating stable performance. The DFT studies confirm molecular-level interactions within the hydrogel heterostructure.
Keywords: dendrite inhibition; flexible rechargeable zinc metal battery; high cation transference number; self-healing hydrogel polymer electrolyte

Strategies to mitigate interlayer porosity in the laser-directed energy deposition process - Jha, Arkajyoti; Ramji, M.; Torris, Arun; Gopinath, Muvvala (Journal of Manufacturing Science and Engineering-Transactions of the ASME, 2026)
Laser-directed energy deposition (L-DED) offers unique advantages for fabricating large-scale metallic components and repairing high-value parts. However, recurring interlayer porosity, particularly while depositing targeted geometry and dimensions, remains a major limitation affecting structural integrity. In this study, systematic deposition strategies were developed to mitigate interlayer porosity by controlling track overlap and optimizing energy apportionment, the two aspects that have not been reported together in previous L-DED studies. Experimental analysis showed that increasing the percentage overlap from 30% to 40% significantly reduced porosity, whereas defining the overlap based on the full width at half maximum (FWHM) provided a more geometry-representative approach. A 30% FWHM overlap was found to be most effective in disrupting periodic porosity recurrence. Additionally, introducing skewed track alignment minimized valley-to-valley overlap across layers, further reducing defect formation. Complementary to geometric strategies, interlayer laser polishing with circular and line beams facilitated pore closure while refining the interlayer microstructure. A key novelty of this work lies in coupling overlap optimization with energy apportionment between powder and substrate, achieved by adjusting the stand-off distance (SoD), which is quantified by a unique experimental approach. This enhanced molten pool flow and ensured improved remelting of the previously deposited layer, which, when combined with a 30% FWHM overlap, effectively eliminated visible interlayer porosity, validated by micro-computed tomography analysis. The integrated approach of optimized overlap, energy apportionment, and interlayer polishing enabled defect-free fabrication of straight walls as well as complex turbine blade profiles, while simultaneously enhancing strength and ductility.
Keywords: Additive manufacturing; energy apportionment; interlayer porosity; laser polishing; laser-directed energy deposition; Micro-computed tomography